Plasma cells are not restricted to the CD27+ phenotype: characterization of CD27-CD43+ antibody-secreting cells - Covens, Kris; Verbinnen, Bert; de Jong, Britt G.; Moens, Leen; Wuyts, Greet; Verheyen, Geert; Nys, Kris; Cremer, Jonathan; Smulders, Stijn; Schrijvers, Rik; Weinhäusel, Andreas; Vermeire, Séverine; et al. (Frontiers in Immunology, 2023)
Circulating antibody secreting cells are present in peripheral blood of healthy individuals reflecting continued activity of the humoral immune system. Antibody secreting cells typically express CD27. Here we describe and characterize a small population of antibody secreting class switched CD19+CD43+ B cells that lack expression of CD27 in peripheral blood of healthy subjects. In this study, we characterized CD27-CD43+ cells. We demonstrate that class switched CD27-CD43+ B cells possess characteristics of conventional plasmablasts as they spontaneously secrete antibodies, are morphological similar to antibody secreting cells, show downregulation of B cell differentiation markers, and have a gene expression profile related to conventional plasmablasts. Despite these similarities, we observed differences in IgA and IgG subclass distribution, expression of homing markers, replication history, frequency of somatic hypermutation, immunoglobulin repertoire, gene expression related to Toll-like receptors, cytokines and cytokine receptors, and antibody response to vaccination. Their frequency is altered in immune-mediated disorders. Conclusion: we characterized CD27-CD43+ cells as antibody secreting cells with differences in function and homing potential as compared to conventional CD27+ antibody secreting cells.